Compare the Histology and Fetal Outcome in Patients with Normal Placenta and Abruptio Placenta (Medical Forum Monthly, 2020)
Objective: To examine the histological examination of abruptio placenta in normal/term delivery and compare with normal placentae also compare the fetal outcomes.Study Design: Comparative/Observational study.Place and Duration of Study: This study was conducted at the Department of Obstetrics & Gynaecology, Women and Children Hospital Abbottabad from April 2019 to December, 2019.Materials and Methods: Sixty-four women with term pregnancy were included in this study. Patients categorized into two groups, group A contains 32 women with abruption placentae and group B 32 women with normal placentae. Patients detailed demographics including age and body mass index were recorded after written consent. Histological examination was done and compares the findings between both groups. Fetal outcomes such as birth weight and Apgar score were examined and compare.Results: Mean BMI of patients in group A was 24.22±2.86 kg/m2 and group B it was 24.78±2.64 24.22±2.86 kg/m2. No significant difference was observed regarding age between both groups p-value >0.05. A significant difference was found regarding fibrinoid necrosis between group A and B (10.8±1.74 Vs 5.57±1.94) with p-value <0.05. Mean syncytial knots in group A was 47.85±9.74 and in group B it was 28.89±4.85, a significant difference was observed between group A and B (p=value <0.0001). Fetal weight was significantly less in group A when compared to group B with p-value 0.001.Conclusion: Women with abruption placentae had significantly worst histological findings and poor fetal outcomes as compared to women with normal placentae.